Son dönem Osmanlı aydınlarının kadının toplumsal hak ve hürriyetlerine bakışları - Dinç, Emine Nurefşan (My University, 2001)
Tez metni bir girişten ve iki bölümden oluşmaktadır. Girişte son dönem Osmanlı toplum yapısı hakkında bilgi verilmekte, gazete ve dergiler zâviyesinden sosyal âlem resmi çizilmektedir. Birinci bölümde Osmanlı toplumunda kadın hayâtına umûmî bir bakış yapılmıştır. İlk kısımda, âilenin teşekkülünde ve dağılmasında kadının rolü ve kadının âile içerisindeki mevkii anlatılmaktadır. Bu çerçevede harem hayâtına, câriyelik müessesesinin işleyişine temâs edilmektedir. Kadının sosyal hayattaki yerini konu alan kısımda kadının ev hâricindeki durumu ve faaliyetleri ile ilgili topluma hâkim kanaatlara yer verilmekte, daha sonra kadının tolum hayâtına daha aktif bir çekide katılmaya başlaması Osmanlı toplumunun Batılılaşması muvâcehesinden ele alınmaktadır. Kadınların son dönemde kurdukları dernekler ve çıkardıkları dergiler hakkında bilgi verilmektedir, bir sonraki bölüm, Osmanlı kadının iktisâdî hayattaki yerini konu almaktadır. Kadının eğitiminin konu alındığı kısımda ise kadın eğitimi ile ilgili olarak topluma hâkim kanaatlardan bahsedilmekte, modernleşme döneminde kızların eğitilmesi için açılan okullar hakkında bilgi verilmektedir. Son olarak Osmanlı kadın kıyâfetleri tanıtılmaktadır. İkinci bölümde, kadın konusunun bir mesele olarak gündeme gelmesi ve bu mesele etrâfında dönemin düşünce akımları arasında cereyân eden belli dergi muhitleri çerçevesinde ele alınmaktadır. İlk kısımda kadın konusunun gündeme taşınması, kadın hareketi, kadın dergilerinde kadınlar tarafından dile getirilen istekler, edebiyat ve tiyatro eserlerinde kadın meselesinin nasıl işlendiği hakkında bilgi verilmektedir. İkinci kısımda kadının sosyal hayâta nasıl katılacağı, çalışması, eğitimi, kıyâfeti, âile içerisindeki mevkii, âilenin kurulmasındaki ve dağılmasındaki rolü gibi kadınla ilgili en çok tartışılan konularda, aydınların görüşleri, kadınların talepleri aktarılmıştır. Son kısımda ise toplumsal bir mesele olarak kadın meselesi hakkında fikir akımlarının görüşleri, bakışları özetlenmiştir.

This study consists of an introduction and two main sections. In the introduction, importance of this study, general works of traditional Ottoman society structure, movements of westernisations in Ottoman society thoughts of Ottoman intelligentsia lived in the last period for westernizations are mentioned. In the first section, focusses on traditional life of Ottoman woman in Ottoman society. In the first part, role of woman in beginning and ending of family and place of woman in Ottoman family are mentiened. In this framework, construction family activities of divorce, poligamy, harem and slave woman in harem in traditional Ottoman society are mentioned basicly. In the part that mentioned place of woman in social life; Ottoman society's thoughts about place and activities of woman outside the house and increasing role of woman in social life in Ottoman society and chances in the thoughts and beliefs about these topics are also mentioned in the frame work of westernization. Following this, acceptances concerning the outside clothing of women, which is closely related to their participation in social life are discussed and the clothes worn by Ottoman women outside their homes are depicted. And then, information is supplied about the position of the Ottoman women in courts, their participation in cherities, societies founded by women and magazines published by them. The topic of the following part is the role of the Ottoman women in the economic life. That part which concerus the education of woman discusses prevailing acceptances on this subject and gives information about the schools founded for girls during the age of modernization. The second chapter discusses, with reference to the main circles of the era, the appearrance of the topic of women as an issue and the debates that arouse betweeen various schools of thought. Firstly, the transfer of the issue into the agenda is discussed. In relation to this subject. İnformation is given revarding the women's movement that arouse in the Ottoman society, the activities of missionaries, treatment in the literary works of the era, of the issues concerning women and Ottoman society's adoption of the developments in the west. And the second part of this chapter discusses the issues concerning women that were most frequently argued among intellectuals of the era. Among them are narrated firstly the debates of intellectuals concerning the participation of women in social life, their working, and clothing in accordance with the İslamic principles (tesattur). As in that part wich concerns the issues concerning the family is discussed the role played by woman in both the formation end the disintegration of the family, those demands that relate to the place of women in the family, and the relevant paragraphs of the legislation that concern the family's rights. And the following part concerns the views of intellectuals and women's demands about the education of women. The last part summarizes the various views of the currents of thought on this question as a social issue.
Keywords: KADIN HAKLARI_TÜRKİYE; Kadınlar; OSMANLI TARİHİ-SON DÖNEM; Siyasal bilimler (Siyaset bilimi); Toplum bilimleri; Yurttaşlık hakları ve siyasal haklar